Políticas de qualificação profissional no Brasil em reformas: um estudo comparativo entre o PLANFOR e o PNQ - Rodrigues, Carolina Gagliano (2013)
In Brazil, the Federal Constitution of 1988 brings with it new institutional arrangements that allow for the participation of society in the deliberations about public policy, albeit in a very restricted way. Framed up among these institutions the Deliberative Council of the Worker Support Fund (CODEFAT), created to manage and deliberate on the public employment policies financed by the Worker Support Fund (FAT), among which we highlight the policies of professional qualification. Considering the qualification as a social and political construction permeated by the dispute between actors with different interests, we have analyzed comparing two programs enrolled in the basic mode of professional education, funded by the FAT and managed by CODEFAT: PLANFOR, prevailing during the Cardoso administration, and PNQ initiated under Lula extending the Dilma government. Both programs are written in governments with different political and ideological orientations. The first adopts policies liberalizing nature, while the second rescues policies of income distribution and increases the emphasis on social programs. In this sense, we investigated whether there are or not significant differences between these two programs focusing on two specific issues: the concept of professional qualifications adopted and the importance attached to social participation, through CODEFAT, on the construction and deliberation on the said policy